Retrospective analysis of array of the published patents, characterizing development of the cast-rolling modules at 2000-2013 in Ukraine and Russia - Бережной, Николай Николаевич; Чубенко, Виктория Анатольевна; Хиноцкая, Алла Анатольевна; Мацышин, Сергей Олегович; Шепель, Анна Александровна; Чубенко, Валерий Андреевич (Technology audit and production reserves, 2015)
It is performed a retrospective research of an array of published patents, characterizing the development of the casting-rolling units for the period 2000-2013 in Ukraine and Russia. These researches identify the relevance of the work to improve the casting-rolling units, the dynamics of the rolling production in general and the production of steel in the casting-rolling unit, which allowed to determine the direction of future research. The research showed that during this period there is a continuous development and improvement of the combined processes of casting-rolling both in Ukraine and in Russia. In Ukraine in 2004 the intensity of the development of this area has increased, reached a peak in 2010, in 2013 decreased slightly, but it was no less than 2004. These researches have allowed to identify disadvantages in the development of casting-rolling units, which are as high temperature of metal casting. It is therefore necessary to make decisions that will reduce the ability to quickly become overheated during casting and create the additional crystallization centers inside the metal.